2014
DOI: 10.7860/jcdr/2014/8058.5225
|View full text |Cite
|
Sign up to set email alerts
|

Association of Salivary Cortisol and Anxiety Levels in Lichen Planus Patients

Abstract: Background: Oral lichen planus (OLP) is a frequently encoun tered chronic inflammatory disease of oral mucosa and skin, where the patients often relate the onset and aggravation of oral symptoms to increased levels of stress. Cortisol, also called as "stress hormone" has been used as an indicator in various stress evaluation studies. Aim:The aim of this crosssectional study was to determine any association between anxiety and salivary cortisol levels in OLP patients. Materials and Methods:A total of 20 OLP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 11 publications
6
48
0
2
Order By: Relevance
“…The mean salivary cortisol level in our group of OLP patients amounted to 0.83 ± 0.40 µg/dL which was higher than the mean of the control group, in concordance with many earlier studies [11,16,[18][19][20] , but the absolute value is lower than that reported in few of these studies [11,16,19,20] . This higher mean cortisol level could be attributed to the earlier time of saliva collection in our study as compared to other studies.…”
Section: Salivary Cortisolsupporting
confidence: 91%
See 2 more Smart Citations
“…The mean salivary cortisol level in our group of OLP patients amounted to 0.83 ± 0.40 µg/dL which was higher than the mean of the control group, in concordance with many earlier studies [11,16,[18][19][20] , but the absolute value is lower than that reported in few of these studies [11,16,19,20] . This higher mean cortisol level could be attributed to the earlier time of saliva collection in our study as compared to other studies.…”
Section: Salivary Cortisolsupporting
confidence: 91%
“…The mean rank of salivary cortisol in OLP patients was not statistically significantly higher than the control group. This insignificance is in concordance with Girardi et al [22] but dissimilar to other studies [11,16,18,19,20] .…”
Section: Salivary Cortisolsupporting
confidence: 88%
See 1 more Smart Citation
“…Salivary cortisol values in OLP group was higher than normal range 32.56 ± 14.52 ng/ml, which was in accordance with Girardi C et al 22 , Rabiei M et al2012 23 , Mohan et al 24 observed higher stress, anxiety and depression levels and higher salivary cortisol values than normal range. Nadendla LK et al 25 observed higher salivary cortisol level which was 17.0 ± 3.82 ng/ml compared to normal individual.…”
Section: Discussion:-supporting
confidence: 85%
“…Emerging evidences are suggesting that psychogenic factors such as anxiety, depression, and stress play important roles in the onset and progression of OLP . A high salivary cortisol level positively correlated anxiety was also showed in patients with OLP . Notably, psychological functions could have a direct impact on the telomere/telomerase system .…”
Section: Discussionmentioning
confidence: 95%